Revising the cosmological constant problem through a fluid different from the quintessence - Orlando Luongo (Physical Sciences and Technology, 2022)
The role of a scalar field is reexamined through the introduction of a quasi-quintessence model. Unlike quintessence, in the quasi-quintessence model, the pressure of the scalar field does not depend on its kinetic energy. This research note provides an overview of the main characteristics of this scenario and outlines how cosmic fluids can be constructed based on quasi-quintessence. A significant application of quasi-quintessence is presented, starting with a reference to Weinberg's no-go theorem, related to the cosmological constant problem. By assuming the occurrence of a phase transition induced by a fourth-order quasi-quintessence potential and suggesting that the violation of the no-go theorem happens exclusively during this phase transition, it is possible to argue a mechanism for addressing the cosmological constant problem. This mechanism involves a form of vacuum energy cancellation, offering a potential solution to the long-standing cosmological constant problem. The discussion also delves into the avoidance of fine-tuning adjustments and explores the implications of this approach in the realms of dark energy and inflation. Physical consequences of the quasi-quintessence scenario are presented, shedding light on its potential benefits and drawbacks.